News Reports on Indonesia’s Post-election 2024 from Selected National and International Newspaper: A Pragmatic Analysis - Pranoto, Budi Eko (UIN Salatiga, 2024)
The Indonesia’s presidential election 2024, as one of the largest democratic nations, gained wide attention from both national and international media. This research carries out a pragmatic analysis of news report on the post-presidential election of Indonesia 2024 from selected national and international newspapers using Austin (1962) and Searle’s (1969) Speech Act Theory. 30 utterances were purposively taken from three newspapers (The Jakarta Post, The Guardian, and The New York Times). By implementing qualitative research method, this research analysis discussed three aspects of Speech Acts: locutionary, illocutionary, and perlocutionary. The result of the analysis showed that there was obvious finding on the reporting style of newspapers on the election outcome. Based on the analysis, assertive statements were dominantly found as it is in line with the nature of newspaper style; present factual information impartially, aiding in neutral and concise reporting. Directive statements wielded figures’ influence and attitudes toward ongoing issues. Commissive speech acts conveyed promises, pledges, and accusations persuasively, while declarative ones declared figures’ initiatives and actions on issues. Expressive speech acts reflected collective societal feelings, particularly regarding election outcomes.